2021
DOI: 10.1016/j.ejro.2021.100337
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiograph in hospitalized children with COVID-19. A review of findings and indications

Abstract: COVID-19 clinical manifestations and radiological findings are milder and less specific in children.• The presence of fever, and fever duration are clinical findings associated with pathological chest imaging.• The most common pattern seen in pathological chest X ray were bilateral diffuse interstitial pattern followed by perihilar bronchial wall thickening.• Consensual specific age-adjusted protocols regarding chest imaging indications in pediatric COVID-19, as the one developed, are needed.• Imaging should n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In the pediatric population, diffuse GGO appearance was the most common finding in the chest CT studies similar to that in adults, followed by patchy consolidation [33,39]. In some studies, the most frequent involvement of COVID-19 pneumonia was reported as the bilateral diffuse interstitial pattern and multifocal involvement in children [5]. In our study group, single lobe involvement was observed in all cases while multifocal involvement was not detected in any of our cases.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the pediatric population, diffuse GGO appearance was the most common finding in the chest CT studies similar to that in adults, followed by patchy consolidation [33,39]. In some studies, the most frequent involvement of COVID-19 pneumonia was reported as the bilateral diffuse interstitial pattern and multifocal involvement in children [5]. In our study group, single lobe involvement was observed in all cases while multifocal involvement was not detected in any of our cases.…”
Section: Discussionsupporting
confidence: 68%
“…As of December 19, 2021 the disease remains a global threat with over 275 million cases and 5 million deaths being reported in a period of nearly two years [4]. In the adult population, the clinical course of SARS-CoV-2 infections ranges from mild to severe respiratory tract disease (with pneumonia usually being a prominent clinical finding) and death, whereas in children, the infection is mostly asymptomatic or milder forms of the disease are reported with a wider clinical manifestation range and low hospitalization and mortality rates [5,6]. During the early period of the pandemic, chest radiography (chest-X ray, CXR) was preferred as the primary imaging modality for clinical monitoring and treatment adjustment in adult patients with COVID-19 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although vertical transplacental transmission of COVID-19 and severe cases of neonatal COVID-19 infections have been reported, the overall literature on the maternal transmission of COVID-19 remains relatively sparse at this time and is under investigation 19–22 . Based on reported cases thus far, chest radiographs range from clear to diffusely opacified in an interstitial and/or airspace distribution 23,24 …”
Section: Spectrum Of Neonatal Lung Disordersmentioning
confidence: 99%
“…[19][20][21][22] Based on reported cases thus far, chest radiographs range from clear to diffusely opacified in an interstitial and/or airspace distribution. 23,24 Pulmonary Interstitial Emphysema (PIE)…”
Section: Neonatal Pneumoniamentioning
confidence: 99%
“…The most frequently observed imaging abnormalities are prominent peribronchial markings and hyperinflation, while consolidation or ground-glass opacity affecting the lower lobes occurs in the most severe forms. 25 As suggested by the majority of the experts, 26,27 chest radiography is considered the most appropriate first step in children not responding to outpatient management and requiring hospitalization.…”
Section: Chest Radiographymentioning
confidence: 99%